A macrophage-based cell therapy approach for the treatment of non-healing diabetic wounds - Boodhoo, Kiara (Stellenbosch : Stellenbosch University, 2023)
Boodhoo, Kiara. 2023. A macrophage-based cell therapy approach for the treatment of non-healing diabetic wounds. Unpublished doctor's dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/b6c690c3-b303-4a9e-8833-0c650c058271